P116 A peer-led programme to improve access to endoscopy training. (19th June 2022) - Chatterjee, Devnandan; Shalabi, Ahmed; Ha, Sun; Dyall, Lovesh; Pomfret, Suzanne; Haycock, Adam
Abstract : Introduction: Endoscopy training has been significantly impacted by the COVID-19 pandemic. The Joint Advisory Group on GI Endoscopy issued guidance for the recovery of endoscopy training. This provided us with an opportunity to improve endoscopy training with a peer-led programme. Methods: The programme involved a group of trainees using the EndoVault ® endoscopy system to scrutinise endoscopy lists to establish their suitability for training. A senior trainee was tasked to allocate the endoscopy lists based on trainee availability and current training objectives. The allocations were made on a 2-weekly cycle. We analysed the number of procedures over a 4-month period (1 st March-30 th June) for 2019, 2020 and 2021. Trainee satisfaction for 2021 was assessed pre- and post-intervention using a Likert scale based survey. Results: There was a significant increase in the number of training procedures performed by trainees, comparing 2019 (pre-pandemic) and 2021 (post-intervention) – 21.7% vs. 59.8%, p<0.0001. The greatest increase was access to training in colonoscopy (297%), with also increased access for gastroscopy (270%) and flexible sigmoidoscopy (242%), represented as the change in the proportion of available training procedures performed by trainees comparing 2019 to 2021. Furthermore, trainees performed more independent procedures. Table 1 summarises the number of endoscopic procedures identified and performed by trainees during 2019, 2020 and 2021 (with *denotes p<0.001 relative to 2019 data and + denotes p<0.001 relative to 2020 data for comparator proportions represented). The survey showed an improvement in satisfaction of trainees' access to endoscopy with 100% of all responding trainees (n=16) being satisfied (25% pre-intervention). 87.5% of all trainees advised the programme helped them to meet their endoscopy training objectives. Conclusions: This programme, devised by trainees for trainees, had a significant improvement in access to endoscopy training. This was further reflected in the results of the satisfaction survey. This programme could easily be applied at other hospital trusts as a model of training delivery.